Multicenter, prospective feasibility study of Nano-Pulse Stimulation™ technology for the treatment of both nodular and superficial low-risk basal cell carcinoma - Ross, Amy S.; Schlesinger, Todd; Harmon, Christopher B.; Moy, Ronald L.; Rohrer, Thomas E.; Mehregan, Darius R.; Nuccitelli, Richard; Johnston, Lauren Jauregui; Knape, William A. (Frontiers in Oncology, 2022)
Nano-Pulse Stimulation™ (NPS™) therapy is a new, non-thermal bioelectric modality that applies ultrashort pulses of electric energy to trigger regulated cell death (RCD) in treated tissues. Instead of initiating necrosis by heating or freezing, NPS therapy permeabilizes intracellular organelles to activate the cell’s own self-destruct pathway of programmed or regulated cell death. Unlike cryotherapeutic procedures that can both damage structural tissues and diffuse into the periphery beyond the margins of the lesion, NPS therapy only affects cells within the treated zone leaving surrounding tissue and acellular components unaffected. In this study we treated 33 basal cell carcinoma lesions on 30 subjects (NCT04918381). The treated lesions were photographed on 3-, 7-, 14-, 30- and 60-days after treatment. All subjects then underwent surgical excision for histological examination of the treated tissue. 92% of the BCC lesions (34 of 37) showed complete histological clearance of BCC. Histologic analysis of the 3 cases where residual BCC was noted indicated that full energy coverage was not achieved, which could be remedied with an improved treatment guide to standardize and optimize the CellFX® procedure based on NPS technology. The CellFX procedure was shown to be safe and effective for the treatment of low-risk nodular and superficial BCC lesions.